Silk Fibroin/Silk Braiding Fabric Composite Grafts via Layer-by-Layer Self-Assembly: Water Permeability and Cytocompatibility. Issue 1 (31st December 2023) - Yu, Yangxiao; Song, Guangzhou; Dai, Mengnan; Meng, Lingpeng; Xu, Jianmei; Fan, Qingmin; Dong, Fenglin; Yin, Yin; Wang, Jiannan
ABSTRACT: Stent grafts play an important role in sealing vessel perforations, ruptures or aneurysms for remodeling vascular access, but maintaining long-term patency remains a major challenge after implantation. Silk fibroin (SF) is an ideal vascular graft material with excellent biocompatibility and physicochemical properties. In this study, we developed a series of composite grafts consisting of regenerated SF (RSF) and silk fabric, prepared using braiding technology and layer-by-layer (LBL) self-assembly, and investigated morphology, water permeability and cytotoxicity. The results showed that silk fabrics were covered effectively and tightly by RSF films, and the anti-water permeability of grafts was closely related to fabric structural parameters and self-assembly layers, in which the braiding angle of 90° and number of axial yarns above 60 threads/10 cm obtained very low water leakage. In particular, the graft prepared by 1 × 2 silk yarn had a thinner and more uniform thickness (70–80 μm), and showed lower water permeability (8.8 mL/min·cm 2 ). Tests on L929 fibroblast cells showed that grafts had no significant cytotoxicity, and unreacted substances could be removed by LBL rinsing. These composite grafts may be promising biomaterials for the repair and regeneration of vascular access.